1467Interaction effects of multimorbidity and frailty on adverse health outcomes in elderly hospitalised patients. (2nd September 2021) - Lujic, Sanja; Randall, Deborah; Simpson, Judy; Falster, Michael; Jorm, Louisa
Abstract: Background: Multimorbidity and frailty are each known to be drivers of adverse outcomes, but their joint effects are less well known. Methods: We used state-wide hospital and mortality data for persons aged ≥75 years, admitted during 2010-2012 in New South Wales, Australia, to ascertain multimorbidity, frailty risk and outcomes: prolonged length of stay (LOS), 30-day mortality and 30-day emergency readmission. We estimated the relative risk (RR) of each outcome using Poisson models with random intercept for hospital. Interactions on both additive and multiplicative scales were examined. Results: Among 257, 535 elderly inpatients, 33.6% had multimorbidity and elevated frailty risk, 14.7% had multimorbidity only, 19.9% had elevated frailty risk only and 31.8% had neither. Additive interactions were present for all outcomes, with a further multiplicative interaction for mortality and LOS. Mortality risk was 4.2 (95% CI 4.1 – 4.4), prolonged LOS 3.3 (95% CI 3.3 – 3.4) and readmission 1.8 (95% CI 1.7 – 1.9) times higher in patients with both factors present compared with patients with neither. Conclusions: Multimorbidity and frailty coexist in older hospitalized patients and interact to increase the risk of adverse outcomes beyond the sum of their individual effects. Their joint effect should be considered in health outcomes research and when administering hospital resources. Key messages: Multimorbidity and frailty coexist and interact to increase the risk of adverse outcomes in hospitalised patients. Research and health planners should consider their joint effects to ensure patients at the highest risk of adverse outcomes are identified.